Outcomes of prevention of HIV mother-to-child transmission in Cipto Mangunkusumo Hospital - Dina Muktiarti; Nia Kurniati; Arwin Akib; Zakiudin Munasir (Indonesian Pediatric Society Publishing House, 2012)
Background Human immunodeficiency virus (HIV) infection is increasing worldwide. One foute of HIV transmission is from mother to child, during pregnancy, delivery or breastfeeding. Prevention of mother􀁂to􀁂child transmission may be an effective strategy to reduce the cases of new HIV infections. Objectives To investigate the incidence of HIV infection in infants born to mothers with HIV and who received prophylactic therapy at birth, as well as to note the outcomes of HIVinfected children in this program. Methods This retrospective study was carried out over a 9􀁂year period, from January 20 03 to December 2011. The participants were HIVexposed infants who attended the HIV clinic, at the Department of Child Health, Cipto Mangunkusumo Hospital, Jakarta. Infants were treated according to the prevention of mother􀁂to􀁂child transmission (PMTCT) protocol at CMH. Parents' and infants' data was recorded. The end point of this study was recording of HIVinfection status in the infants. Results There were 238 infants included in this study. HIV infection was confirmed in 6 (2.5%) infants, while 170 (71.4%) subjects were uninfected, and 62 (26.1%) subjects were lost to follow􀁂up. No subjects who underwent complete PMTCT management were infected. Most subjects were male, full􀁂tenn, and delivered by caesarean section in our hospital. The most frequently observed parental risk factor was intravenous drug use. Maternal antiretroviral therapy (ART) was given during pregnancy in most cases. Morbidities in all subjects were low. Conclusion The PMTCT program at CMH was effective for reducing the number ofHIVinfected infants from mothers with HIY. [Paediatrlndanes. 2012;52:294-9].